2003
DOI: 10.1002/jbm.a.10017
|View full text |Cite
|
Sign up to set email alerts
|

Interactions of fibrinolytic system proteins with lysine‐containing surfaces

Abstract: Studies on the interactions of tissue plasminogen activator (tPA) and plasminogen with polyurethane surfaces containing epsilon-lysine moieties (epsilon-amino group free) are reported. These surfaces are considered to have the potential to dissolve nascent clots that may be formed on them. For adsorption from both single protein solutions and plasma, the surfaces were found to have a high capacity for tPA as well as plasminogen. A significant fraction of preadsorbed tPA was displaced from the epsilon-lysine su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
24
0

Year Published

2006
2006
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 46 publications
(24 citation statements)
references
References 20 publications
0
24
0
Order By: Relevance
“…It does not inhibit synthetic substrate hydrolysis by plasminogen activators as well as hydrolysis synthetic substrate and protein degradation by plasmin. EACA binds to lysine binding sites (LBS) in plasminogen activators, plasminogen (free and in SK or SFK complex) and plasmin molecules (7, 8, The optimal distance between these groups is 0.68 nm (10). A decrease or an increase of this distance results in a reduction or a disappearance of antifibrinolytic activity (11,12).…”
Section: Mechanism Of Antifibrinolytic Activitymentioning
confidence: 99%
“…It does not inhibit synthetic substrate hydrolysis by plasminogen activators as well as hydrolysis synthetic substrate and protein degradation by plasmin. EACA binds to lysine binding sites (LBS) in plasminogen activators, plasminogen (free and in SK or SFK complex) and plasmin molecules (7, 8, The optimal distance between these groups is 0.68 nm (10). A decrease or an increase of this distance results in a reduction or a disappearance of antifibrinolytic activity (11,12).…”
Section: Mechanism Of Antifibrinolytic Activitymentioning
confidence: 99%
“…Moreover, plasminogen appeared to be bound to material surfaces in a way that facilitates its activation to plasmin by t-PA, similar to plasmin formation on the surface of fibrin. These surfaces were also demonstrated to have the ability of clot lysis and the potential to be fibrinolytic [43,44].…”
Section: Loading Bioactive Molecules To Inhibit the Activation Of Hummentioning
confidence: 96%
“…Such a surface would mimic the naturally occurring fibrinolytic process that occurs on the surface of fibrin [8]. This concept has been pursued in our laboratories over the past several years [9][10][11][12][13][14][15][16][17][18][19][20][21]. The present contribution is intended, in part, as an elaboration of this concept and an outline of developments to date.…”
Section: Introductionmentioning
confidence: 92%
“…Therefore, it was appropriate to investigate the interactions of t-PA with our "plasminogen-exclusive" lysinized PU surfaces. Detailed studies of t-PA binding to these surfaces and the fate of adsorbed t-PA on exposure to plasma were undertaken [16]. The data obtained indicated that the -lysine surfaces had a high capacity for t-PA adsorption from buffer.…”
Section: Fibrinolytic Surface With Lysine-rich Coatingsmentioning
confidence: 99%